Graduation of Cooperatives.Strengthening Rural Associative Enterprises (RAEs) through a graduation process - Chavarría Salguera, Jimmy Antonio; Maradiaga Corea, Marco Antonio; Palma, Johseelyn; Martínez Blandón, Juan Carlos (Catholic Relief Services, 2015)
This publication is the product of a participatory capitalization process facilitated by the International Center for Tropical Agriculture (CIAT) for the Program for Rural Enterprise Management, Health, and the Environment (PROGRESA.) This document seeks to reflect the organizational and business strengthening experience facilitated by 33 RAEs involved in the project, which are located in the departments of Jinotega, Matagalpa, Madriz, and Nueva Segovia, and take part in the three value chains served by PROGRESA: beans, fruits and vegetables, and dual-purpose cattle. Seven organizations are part of the fruits and vegetables value chain, 12 are engaged with beans, and 26 with cattle.